Technology of Accelerated Knowledge Transfer for Anticipatory Training of Specialists in Digital Economy - Gitelman, Lazar Davidovich; Kozhevnikov, Mikhail Viktorovich; Ryzhuk, Olga Borisovna (Economy of Regions, 2020)
The training of digital economy specialists requires new approaches to the educational process, which should contain updated training materials and flexible teaching formats and methods. Moreover, it should create competencies for working in the conditions of uncertainty and maintain readiness to solve complex problems in the process of professional activity. Close integration of scientific and educational activities is the only possible approach to attain this goal. Thus, we suggested a mechanism for rapidly transferring the latest results of scientific research to the educational process at universities in order to organize anticipatory learning. We demonstrated the organizational principles, content and methods of this mechanism on the example of managerial training. We have substantiated and described the research area «Pre-emptive management in rapidly developing industries and sectors», as well as the key provisions of anticipatory learning and its knowledge base. Further, we have discussed the possibilities of applying the technology platforms for designing branded educational products with flexible modular structure. Thanks to such structure, the training programs function as a continuous conveyor for continuous competency building. In the paper, we present a conceptual project and an operational mechanism of a university-based scientific and educational platform. Testing on the Ural Federal University (UrFU) has proved the efficiency of the suggested methods and validity of the research results. The proposed platform can be used for establishing world-class Research and Educational Centres in the region aimed at developing global research and industrial cooperation in order to create breakthrough innovations.